1990
DOI: 10.1302/0301-620x.72b5.2211753
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous or staged bilateral total knee replacements in rheumatoid arthritis. A prospective study

Abstract: In a prospective study of 100 knee arthroplasties in patients with rheumatoid arthritis, simultaneous bilateral surgery was compared with staged bilateral replacements. All patients had improved function following their operations but those who had staged surgery only achieved maximum benefit after the second knee had been replaced. The complication rate was no greater for simultaneous surgery and we therefore advocate the method for those patients who require bilateral replacements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 0 publications
2
38
0
6
Order By: Relevance
“…Other authors have reported these problems when analyzing data from Medicare enrollees [4]. Although differences in outcomes between these different approaches may exist [43,53,60,64,69,73], our data more likely provide an overview of actual practice. Moreover, the average length of hospitalization for patients undergoing BTKA in our analysis (5.8 days) was only a half day longer than that of patients undergoing UTKA (5.3 days), indicating probably in most of the admissions, BTKA was performed under the same anesthetic.…”
Section: Discussionmentioning
confidence: 79%
“…Other authors have reported these problems when analyzing data from Medicare enrollees [4]. Although differences in outcomes between these different approaches may exist [43,53,60,64,69,73], our data more likely provide an overview of actual practice. Moreover, the average length of hospitalization for patients undergoing BTKA in our analysis (5.8 days) was only a half day longer than that of patients undergoing UTKA (5.3 days), indicating probably in most of the admissions, BTKA was performed under the same anesthetic.…”
Section: Discussionmentioning
confidence: 79%
“…Bilateral tibio-femoral joint spaces have been almost closed Fig. 2 Latest anteroposterior A and lateral B radiographs of the patient 2 years postoperatively spent in hospital, reduces anesthesia risks and the side effects of drugs, lowers the cost, saves blood, and facilitates early rehabilitation [4,9]. For those reasons, we prefer to perform simultaneous bilateral TKA on patients with rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…• une prothèse totale d'épaule et une prothèse totale de coude, si les douleurs sont telles aux deux articulations que l'arthroplastie d'une seule articulation laisserait persister des douleurs tellement importantes qu'elles entraveraient considérablement la rééducation [9,10,11] ; cette attitude n'est pas conseillée par tous les auteurs, ainsi Aidem [12], Friedman et Ewald [13] ont réa-lisé ces prothèses dans des temps opératoires diff érents, trois fois sur cinq (21/35) en commençant par le coude, deux fois sur cinq (14/35) en commençant par l'épaule. En revanche, il ne nous semble pas raisonnable de réaliser dans le même temps opératoire deux prothèses totales de genou, en raison du cumul des pertes sanguines, même si plusieurs auteurs n'ont pas rapporté d'augmentation de la morbidité ou de la mortalité d'une telle association [14][15][16][17][18][19][20] ou une faible augmentation [21], voire une faible diminution [22]. Il nous semble préférable de les réaliser à 7-10 jours de délai, même si Liu & Chen [17] n'ont pas vu d'avantage à cette association diff érée par rapport à leur réalisation simultanée ; Bezwada et al [23] ont même plaidé pour une association « rescellement d'une PTG + pose d'une PTG primaire » sans y voir de risque.…”
Section: Arthroplasties Simultanéesunclassified